Is there a traumatic complicated grief? Symptomatological differences between complicated grief after a traumatic and a non-traumatic death - Jiménez-Prensa, Adela; Sanz, Jesús; García de Marina, Andrea; Soriano, Arantxa; S. Marqueses, José Manuel; García-Vera, María Paz (Psicooncología, 2023)
Objective: To examine the existence of complicated traumatic grief as a different construct from complicated grief, analyzing whether the symptoms of complicated grief and post-traumatic stress are different in people who suffer complicated grief after a traumatic and non-traumatic death. Method: A group of 89 mourners with complicated grief after a death from a terrorist attack and a group of 54 mourners with complicated grief after a death due to age or illness completed the Inventory of Complicated Grief (ICG) and versions of the PTSD Checklist Scale (PCL-S or PCL-5). Results: ANCOVA performed on the scores on the IDC items and on the 16 items common to the two versions of the PCL revealed that the two groups of mourners did not differ in any of the symptoms of complicated grief or post-traumatic stress, except in two complicated grief symptoms in which the differences went in opposite directions. Conclusions: Although a traumatic death, such as a terrorist attack, increases the severity of grief reactions and the probability of suffering complicated grief, this complicated grief is similar to what people can suffer after a non-traumatic death, at least concerning its symptoms and the simultaneous symptoms of post-traumatic stress. Therefore, one cannot speak of complicated traumatic grief as different from complicated grief.